Using Reading Response Journals for Reading Comprehension - Lauree M. Buus (Networks: An Online Journal for Teacher Research, 2005)
This action research study is aimed at addressing the memory issues that are seen daily in the classroom. Students in a literature-based reading program used reading response journals to assist in their reading comprehension. Anecdotal observations, journal writing, conferencing, interest surveys, and knowledge-based comprehension tests were used to determine the effectiveness of this approach. Memory has three components: sensory memory storage, short-term memory storage, and long-term memory storage. It is desirable for students to get major concepts into long-term memory and back out when needed. This process includes the steps of encoding, storage, retrieval, and reporting. Many factors can influence these steps. Teaching memory strategies could help improve a student's memory ability. In this study, keeping a reading response journal was the strategy used to reach this goal and subsequently to improve reading comprehension.